2007
DOI: 10.1016/j.micres.2006.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential for plant growth promotion in groundnut (Arachis hypogaea L.) cv. ALR-2 by co-inoculation of sulfur-oxidizing bacteria and Rhizobium

Abstract: The use of Rhizobium inoculant for groundnut is a common practice in India. Also, co-inoculation of Rhizobium with other plant growth-promoting bacteria received considerable attention in legume growth promotion. Hence, in the present study we investigated effects of co-inoculating the sulfur (S)-oxidizing bacterial strains with Rhizobium, a strain that had no S-oxidizing potential in groundnut. Chemolithotrophic S-oxidizing bacterial isolates from different sources by enrichment isolation technique included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Biomass measurements revealed that this was not the case, and that the differences in metal update by the plants are rather an effect of individual isolates. Synergistic interactions between bacteria in plant growth promotion have been described in numerous other studies (Anandham et al, 2007;Domenech et al, 2006;Kannan and Sureendar, 2009), and it is quite possible that in our study, synergistic interactions amongst bacteria increase root elongation and also act to keep cadmium out of plants.…”
Section: Discussionsupporting
confidence: 68%
“…Biomass measurements revealed that this was not the case, and that the differences in metal update by the plants are rather an effect of individual isolates. Synergistic interactions between bacteria in plant growth promotion have been described in numerous other studies (Anandham et al, 2007;Domenech et al, 2006;Kannan and Sureendar, 2009), and it is quite possible that in our study, synergistic interactions amongst bacteria increase root elongation and also act to keep cadmium out of plants.…”
Section: Discussionsupporting
confidence: 68%
“…Using a clay soil inoculant mix with powdered elemental sulfur, inoculation of sulfuroxidizing bacteria (Thiobacillus sp.) along with rhizobia provided a synergistic interaction that promoted yield and oil content of groundnut in sulfur-deficient soils (Anandham et al 2007).…”
Section: Soil-made Inoculantsmentioning
confidence: 99%
“…The analysis of field soil samples taken after harvest revealed that soil inoculation of SoxB reduced soil pH from 7.8 to 7.5. Anandham et al [19] reported that inoculation of SoxB also increased available soil-S from 7.4 to 8.43 kg ha −1 , and EC from 0.20 to 0.25 dS m −1 . Anandham et al [19] also reported that the soil pH decreased from 7.2 to 7.0; however, no negative effects were evident on plant growth.…”
Section: Changes In Soil Ph In Onionmentioning
confidence: 98%
“…Anandham et al [19] reported that inoculation of SoxB also increased available soil-S from 7.4 to 8.43 kg ha −1 , and EC from 0.20 to 0.25 dS m −1 . Anandham et al [19] also reported that the soil pH decreased from 7.2 to 7.0; however, no negative effects were evident on plant growth. A study on peanut production revealed that application of elemental S (0.6 Mg ha −1 ) and inoculation of Thiobacillus significantly reduced the soil pH from 8.2 to 7.1 at the end of the growing period [20].…”
Section: Changes In Soil Ph In Onionmentioning
confidence: 98%
See 1 more Smart Citation